PEMAHAMAN IBU-IBU PKK KECAMATAN JEBRES TENTANG KEKERASAN DALAM RUMAH TANGGA (KDRT) - Endang Sri Sudalmi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2011)
Abstract The main problem of this research is that still many women who haven’t comprehend. About the home violence, they only know the physical violence, on the other hand there are many more violence is enduring in other forms. The aim of the research is to know whether interpersonal communication done by Kecamatan Jebres Surakarta is supporting team, dealing with home violence is understood by the women in that area. This research used descriptive qualitative method in talking respondence around Kecamatan Jebres Surakarata. The result shown in this research is that the home violence socialization among the women worned well. However they still need more explanation toundersian or to know the other forms of home violence which are stated in the low. It is foud that the husbands do less violence sence their marriage in average, has last for more than 30 years. Hence the families never get trouble dealing with home violence. They live peacefully and put everything on God’S hand. Key Words :Understanding, family harshnees, PKK group.